Applications of Science of Learning Principles to support Teaching and Learning of Cognitive Pattern Recognition - Ling, Meng Kay Daniel (Technium Social Sciences Journal, 2021)
This paper addresses the applications of the science of learning principles to support the teaching and learning of cognitive pattern recognition. The paper first provides a brief introduction to the science of learning and cognitive pattern recognition. Six science of learning principles have been identified to be relevant to the teaching and learning of cognitive pattern recognition and are discussed individually. The paper also offers suggestions on how to integrate the various science of learning principles for teachers to teach cognitive pattern recognition in the classroom. A teaching process model for cognitive pattern recognition is proposed and developed, which incorporates the various science of learning principles to optimize learning and minimize redundancies. Finally, this paper highlights the implications and provides several recommendations for educators to consider when they decided to incorporate the science of learning principles into their curriculum to teach cognitive pattern recognition.